2009
DOI: 10.1007/s00520-009-0609-3
|View full text |Cite
|
Sign up to set email alerts
|

Reducing gastric secretions—a role for histamine 2 antagonists or proton pump inhibitors in malignant bowel obstruction?

Abstract: Based on well-conducted studies, objective evidence exists that confirms ranitidine will decrease the volume of gastric aspirates. This forms a sound basis from which to develop further research aimed at improving the care of people with malignant bowel obstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…A recent meta-analysis confirmed that ranitidine is more effective than proton pump inhibitors as an antisecretory agent. Based on these data, the authors hypothesized that ranitidine would be useful as an adjuvant drug in antisecretory therapy for the treatment of MBO and suggested the development of specific research to confirm these findings 61,62…”
Section: Treatmentmentioning
confidence: 99%
“…A recent meta-analysis confirmed that ranitidine is more effective than proton pump inhibitors as an antisecretory agent. Based on these data, the authors hypothesized that ranitidine would be useful as an adjuvant drug in antisecretory therapy for the treatment of MBO and suggested the development of specific research to confirm these findings 61,62…”
Section: Treatmentmentioning
confidence: 99%
“…This is brought into sharper focus when the data to support reduction in the volume of secretions in other settings using these medications suggests that they are relatively ineffective. 4 The study by Wildiers et al 1 lacked a placebo arm. Given the current state of knowledge in this field, the high risk of side effects with each of these medications, and the background evidence that intervention and placebo may have the same effect on terminal secretions in this population, the lack of a placebo is a significant omission.…”
Section: To the Editormentioning
confidence: 99%
“…7 A meta-analysis demonstrated superiority of ranitidine over other agents, including proton pump inhibitors, in decreasing the volume of upper gut secretions. 8 These two therapies, therefore, were included in both arms as standard therapies.…”
Section: Introductionmentioning
confidence: 99%